Proyek Sistem Informasi Pengajuan Klaim Asuransi Jiwa Berbasis Web Pada Asuransi Syariah Takaful Keluarga - Pranata, Dicky; Hamid, Muhammad Irfan; Dzariyat, Yolla; Purnamasari, Indah (Teknik Informatika Fakultas Ilmu Komputer, 2026)
The sharia life insurance claim process requires speed, transparency, and compliance with sharia principles. However, at PT Asuransi Takaful Keluarga, the claim process is still handled manually, causing delays, document loss risks, and limited transparency in claim status and Service Level Agreement (SLA) monitoring. This study aims to design and develop a web-based Sharia Life Insurance Claim Submission Information System to automate the end-to-end claim process and improve service efficiency. The developed system provides online claim submission, document upload and verification, real-time claim and SLA monitoring, and audit trail features. System testing was conducted using Performance test, Website safety test, User Acceptance Testing (UAT), and System Usability Scale (SUS). The results show that the system functions properly and achieved a SUS score of 82.5, categorized as Excellent. The system effectively improves efficiency, transparency, and accuracy in the sharia life insurance claim process